Championship interseason period did not reduce knee peak moment : a 10-years retrospective study of 467 elite soccer players - Scoz, Robson Dias; Burigo, Ricardo Lima; Ferreira, Isabella Christina; Ramos, Ana Paula Silveira; Judice, André Filipe Teixeira; Mendes, Jose Joao Baltazar; Ferreira, Luciano Maia Alves; Amorim, César Ferreira (Paradigm, 2022)
Study aim: To compare knee moment profiles of professional soccer players from different playing positions before and after an interseason period. Material and methods: Retrospective study of 467 healthy, professional elite Brazilian soccer players before and after an official championship interseason period during 10-years. Main outcome measures were isokinetic peak moment from knee extensors and flexors from concentric and eccentric contractions. A Two-way ANOVA analysis was used to compare each playing position before and after interseason period. Results: It was found no statistical difference in Ext.CPT (from p = 0.11 to p = 0.97), Ext.EPT (from p = 0.07 to p = 0.85), Flx. CPT (from p = 0.14 to p = 0.90) or Flx.EPT (from p = 0.10 to p = 0.91) between End-Season and Pre-Season evaluations for all playing positions (from Goalkeepers, Defenders, Backsiders, Midfielders and Forwards). Conclusions: Isokinetic peak moment did not have significant differences after an interseason period of 4 to 6 weeks, allowing trainers and coaches to focus their pre-season period on other performance concerns than strengthening.
Keywords: Isokinetic; Strength; Training; Performance; Sport